Pusat Pembinaan Dan Pengembangan Kesenian Wayang Di Bali - Budiarta, I Wayan; Tri Adiputra, I Gusti Ngurah (Jurnal Anala, 2020)
The existence of some puppets show in Bali are significantly marginalized at recently in the midst of any entertaiments growing up. There are a tendency that the puppets show are almoust going to be extinct, for an example Nongnong Kling Puppet at Paksa Bali Village, Klungkung regency. The sacred puppet show was able to be performed until 1988, because its group members are dispersed and there is only one senior dancer still remains. The similar condition was happened at custom village of Manggis, Manggis subdistrik at Karangasem regency. The village had ever possesed a Telek Puppet group at (Wayang Wong/Parwa) as a sacred dance for offering rites/piodalan the Pura Desa temple of Manggis custom village. Waning of the dance was caused by the lack interest of the successor generations (the youth prefer to work on tourism). Meanwhile, at Buduk custom village, Badung regency, there is a Cupak puppet tradition group that is closed to be vanished. Regarding with the extinction tendency of the puppet show group, so it needs establishing a facility as the centre for puppet coaching and developing in Bali. The research uses an inductive approach for constructing some concepts of designing and planning. The concepts were formulated from the intesection of some components, such as : the field observation result, the puppet expertise interview, the study of literatures , the comparative study, the study of some architectural standards and also the study of local government regulation. The designing and planning for the centre of puppet coaching and developing in Bali, in Gianyar regency, are used the basic concept as follwos : recreative, educative, creative and productive which means that the concepts are reformulated from : the functional approach, climate & environment and the social-cultural background. The architecture theme of Neo Vernacular applied in designing and planning for the centre of puppet coaching and developing in Bali, in Gianyar regency intend its façade/physical appearance can be in harmonious matter at the surrondings, but it still has a contemporary building impression. Because the Neo Vernacular architecture is an equivalent combination between the traditional architecture and modern one.